2015
DOI: 10.4103/1658-354x.152891
|View full text |Cite
|
Sign up to set email alerts
|

Novel management of methylene blue extravasation: A case report and review of literature

Abstract: Methylene blue is a highly irritant drug and has been used intraoperatively. Its accidental extravasation can lead to tissue necrosis. In this report, a unique management is described, and the patient recovered without any morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Even there are few complications associated with endoscopic tattooing, they are not limited to issues related to transmural injection. Injection of methylene blue has been reported to cause ulceration and necrosis during breast surgery, cochlear implantation, and laparotomy 3,4. Our case is the first description of a necrotic ulcer due to inadvertent injection in the colon.…”
Section: Case Reportmentioning
confidence: 61%
“…Even there are few complications associated with endoscopic tattooing, they are not limited to issues related to transmural injection. Injection of methylene blue has been reported to cause ulceration and necrosis during breast surgery, cochlear implantation, and laparotomy 3,4. Our case is the first description of a necrotic ulcer due to inadvertent injection in the colon.…”
Section: Case Reportmentioning
confidence: 61%
“…It has been shown that the severity of tissue necrosis is proportional to the solution volume and concentration. 2 In contrast, low concentration of MB dye showed no significant difference in terms of developing complications. 5 MB can be administered safely through peripheral IV routes without any site changes reported.…”
Section: Discussionmentioning
confidence: 92%
“…Numerous underlying mechanisms have been proposed in dye extravasation which includes penetrating the vein wall with the needle or catheter or an inflammatory reaction in the vein which can lead to injury of the vessel endothelium and hence leakage of the infused dye. 2 MB, is a cationic thiazine which causes toxic effects to the tissue by producing free radicals leading to local inflammation and cellular injury. 2 , 4 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations